THE EFFECTS OF AGGLOMERATION ON WAGES: EVIDENCE FROM THE MICRO‐LEVEL1. (23rd April 2013) - Fingleton, Bernard; Longhi, Simonetta
ABSTRACT: This paper estimates individual wage equations to test two rival non‐nested theories of economic agglomeration, namely New Economic Geography (NEG), as represented by the NEG wage equation and urban economic (UE) theory, in which wages relate to employment density. In the U.K. context, we find that for male respondents, there is no significant evidence that wage levels are an outcome of the mechanisms suggested by NEG or UE theory, but this is not the case for female respondents. We speculate on the reasons for the gender difference.